2013
DOI: 10.3892/ijmm.2013.1441
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Koelreuteria henryi Dummer induce apoptosis and autophagy by inhibiting dihydrodiol dehydrogenase, thus enhancing anticancer effects

Abstract: Dihydrodiol dehydrogenase (DDH) is frequently detected in cancer cells, and its overexpression correlates with drug resistance, the downregulation of DNA repair mechanisms, increased frequency of tumor recurrence, cancer cell metastasis and poor prognosis. The silencing of DDH expression using siRNA, on the other hand, reduces drug resistance and cancer cell mobility. These data suggest that DDH may be an oncogene-related protein. However, no specific DDH inhibitor has been identified to date. Thus, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…Interestingly, a previous study reported that long-term exposure of GBM cells to TMZ decreases drug sensitivity by up-regulating the expression of AKR enzymes and glucose transporter [50]. The elevation of glucose transport altered mitochondrial metabolism, while the increase of AKR enzymes deactivated TMZ and cisplatin, supporting our finding that some AKR enzymes were localized on the mitochondria-associated membrane (MAM), the essential organelle that regulates material transport to the mitochondria and nucleus [47,48]. Both transportation passages require DRP1, ATAD3A, and mitofusin 2 (Mfn2) [28,29].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, a previous study reported that long-term exposure of GBM cells to TMZ decreases drug sensitivity by up-regulating the expression of AKR enzymes and glucose transporter [50]. The elevation of glucose transport altered mitochondrial metabolism, while the increase of AKR enzymes deactivated TMZ and cisplatin, supporting our finding that some AKR enzymes were localized on the mitochondria-associated membrane (MAM), the essential organelle that regulates material transport to the mitochondria and nucleus [47,48]. Both transportation passages require DRP1, ATAD3A, and mitofusin 2 (Mfn2) [28,29].…”
Section: Discussionsupporting
confidence: 86%
“…Our previous studies showed that DRP1 is involved in an alternative mitochondrial import route, and the disruption of this route induces autophagy [28,29]. Using DRP1 as a target, we found that several Chinese medicinal herbal extracts (CMHEs) inhibit DRP1 expression, including Astragalus, propinquus, Koelreuteria elegans, Lithospermum erythrorhizon, and Polygala tenuifolia [47]. Using a search engine (http://www.google.com.tw/) to search for the major ingredients of the plants, we found that shikonin from L. erythrorhizon is one of the most promising pure compounds.…”
Section: The Respective Effects Of Shikonin and Saha On Drp1 Expressimentioning
confidence: 99%
“…Elevation of glucose transport altered mitochondrial metabolism, while the increase of Cheng, 18 -AKR enzymes deactivated TMZ and cisplatin, supporting our findings that some of AKR enzymes were localized on the mitochondria-associated membrane (MAM), the essential organelle that regulated material transports to mitochondria and nucleus [38,39]. Both transportation passages require DRP1, ATAD3A, and mitofusin 2 (Mfn2) [25,42].…”
Section: Discussionsupporting
confidence: 74%
“…Our previous studies showed that DRP1 was involved in an alternative mitochondrial import, and disruption of this passage induces autophagy [24,25]. Using Cheng, 15 -DRP1 as a target, we found that several Chinese medicinal herbal extracts (CMHEs) inhibited DRP1 expression, including Astragalus, propinquus, Koelreuteria elegans, Lithospermum erythrorhizon, and Polygala tenuifolia [38]. Using the web engine (http://www.google.com.tw/) to search for the major ingredients of the plants, we found that shikonin from the L. erythrorhizon is one of the most promising pure compounds.…”
Section: The Respective Effects Of Shikonin and Saha On Drp1 Expressimentioning
confidence: 99%
“…Our previous studies showed that DRP1 was involved in an alternative mitochondrial import, and disruption of this passage induces autophagy [24,25]. Using DRP1 as a target, we found that several Chinese medicinal herbal extracts (CMHEs) inhibited DRP1 expression, including Astragalus, propinquus, Koelreuteria elegans, Lithospermum erythrorhizon, and Polygala tenuifolia [39]. Using the web engine (http://www.google.com.tw/) to search for the major ingredients of the plants, we found that shikonin from the L. erythrorhizon is one of the most promising pure compounds.…”
Section: The Respective Effects Of Shikonin and Saha On Drp1 Expressimentioning
confidence: 99%